Consumer Protection of Export Transportation Services in the Case of Crime of Goods Theft (Juridical Analysis at PT. Spice Lines International, Sunggal District) - Sitepu, Dilena; Isnaini, Isnaini; Amal, Ridha Haykal (Journal of Public Representative and Society Provision, 2025)
International trade is an important sector in the Indonesian economy, especially through export activities involving sea transportation services. However, in practice, the process of transporting export goods cannot be separated from various risks, one of which is the crime of theft that causes large losses for business actors. This study aims to analyze the legal responsibility of transportation service providers in the case of theft of export goods, as well as to examine the legal protection of service users, especially PT. Spice Lines International which suffered losses due to theft during sea transportation. The research method used is a normative and empirical juridical approach, with data collection techniques through interviews and documentation studies. The results of the study show that although there are legal provisions governing the responsibility of carriers, their implementation is still weak. Many cases of losses due to theft are not resolved through legal channels due to evidentiary constraints, weak contract clauses, and lack of legal understanding from service users. The legal protection provided by laws and regulations has not been fully effective in guaranteeing the rights of service users to obtain compensation. Therefore, it is necessary to strengthen legal instruments in transportation agreements, improve logistics security systems, and optimize dispute resolution through mediation or arbitration. This study recommends a reformulation of regulations and synergy between stakeholders to create a fairer and more functional legal protection system in the export transportation service sector.